Behavioral Counseling To Reduce Smartphone Addiction In Childern - Laila Maharani (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
Uncontrolled gadget use in children can lead to addiction, characterized by difficulty limiting screen time and impaired learning or social activities. This study analyzes the implementation of behavioral counseling in reducing gadget addiction through a narrative literature review. Findings indicate that gadget addiction is a learned behavior maintained by pleasurable reinforcement. Behavioral counseling reduces this behavior by identifying antecedent-behavior-consequence patterns, monitoring usage, establishing behavioral contracts, applying positive reinforcement, controlling stimuli, and developing alternative activities. Intervention effectiveness is strengthened when parents and teachers consistently enforce rules and model healthy technology use. Ultimately, behavioral counseling aims to establish controlled, functional, and developmentally appropriate digital habits.